Defensa de proyectos de investigación - Llivi Ruilova, Danny Vicente (2023)
In compliance with the established schedule, the defense of the research projects of the UEB Nursing degree was carried out, which was attended by Mgtr. Silvana López Paredes, Dean; members assigned to be part of the courts, family members and special guests.